Models of production runs for multiple products in flexible manufacturing system - Ilić, Oliver; Radović, Milić (Yugoslav Journal of Operations Research, 2011)
How to determine economic production runs (EPR) for multiple products in flexible manufacturing systems (FMS) is considered in this paper. Eight different although similar, models are developed and presented. The first four models are devoted to the cases when no shortage is allowed. The other four models are some kind of generalization of the previous ones when shortages may exist. The numerical examples are given as the illustration of the proposed models.